Immunization coverage and its determinant factors among children aged 12-23 months in Ethiopia: a systematic review, and Meta- analysis of cross-sectional studies - Akine Eshete; Sisay Shewasinad; Solomon Hailemeskel (BMC, 2020)
Abstract Background Immunization is the process by which a person is made immune or resistant to an infectious disease, typically by the administration of vaccine. Vaccination coverage for other single vaccines ranged from 49.1% for PCV to 69.2% for BCG vaccine. The vaccination coverage for basic vaccinations was 39.7% in Ethiopia. There have been epidemiological studies available on immunization in Ethiopia. Yet, these studies revealed a wide variation over time and across geographical areas. This systematic review and Meta-analysis aim to estimate the overall immunization coverage among 12-23 months children in Ethiopia. Methods Cross-sectional studies that reported on immunization coverage from 2003 to August 2019 were systematically searched. Searches were conducted using PubMed, Google Scholar, Cochrane library, and gray literature. Information was extracted using a standardized form of Joanna Briggs Institute. The search was updated 20 Jan 2020 to decrease time-lag bias. The quality of studies assessed using Joanna Briggs Institute cross-sectional study quality assessment criteria. I-squared statistics applied to check the heterogeneity of studies. A funnel plot, Begg's test, and Egger's regression test was used to check for publication bias. Results Out of 206 studies, 30 studies with 21,672 children with mothers were included in the Meta-analysis. The pooled full immunization coverage using the random-effect model in Ethiopia was 58.92% (95% CI: 51.26-66.58%). The trend of immunization coverage was improved from time to time, but there were great disparities among different regions. Amhara region had the highest pooled fully immunized coverage, 72.48 (95%CI: 62.81-82.16). The I2 statistics was I2 = 99.4% (p = 0.0001). A subgroup meta-analysis showed that region and study years were not the sources of heterogeneity. Conclusion This review showed that full immunization coverage in Ethiopia was 58.92% (95% CI: 51.26-66.58%). The study suggests that the child routine immunization program needs to discuss this low immunization coverage and the current practice needs revision.